2008
DOI: 10.1111/j.1365-2249.2008.03711.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal liver function in common variable immunodeficiency disorders due to nodular regenerative hyperplasia

Abstract: SummaryPatients with common variable immunodeficiency disorders are monitored for liver function test abnormalities. A proportion of patients develop deranged liver function and some also develop hepatomegaly. We investigated the prevalence of abnormalities and types of liver disease, aiming to identify those at risk and determine outcomes. The local primary immunodeficiency database was searched for patients with a common variable immunodeficiency disorder and abnormal liver function and/or a liver biopsy. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(144 citation statements)
references
References 23 publications
(39 reference statements)
10
127
1
6
Order By: Relevance
“…There were also positive relationships between the last 2 features and between daily stool frequency and low body weight. Ward et al found similar results in their study suggesting that splenomegaly and hepatomegaly developed either jointly or separately in patients with CVID (23). They also showed a strong association between nodular regenerative hyperplasia of the liver and lymphoproliferation in their patients.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…There were also positive relationships between the last 2 features and between daily stool frequency and low body weight. Ward et al found similar results in their study suggesting that splenomegaly and hepatomegaly developed either jointly or separately in patients with CVID (23). They also showed a strong association between nodular regenerative hyperplasia of the liver and lymphoproliferation in their patients.…”
Section: Discussionsupporting
confidence: 58%
“…In Ward et al 's study, abnormal liver function tests (especially for ALP) and hepatomegaly were present together in some patients with CVID and were associated with elevated GGT (23).…”
Section: Discussionmentioning
confidence: 90%
“…Schistosomiasis [16], toxins/drugs (arsenic [17,18], vitamin A [19], azathioprine [20], 6-thioguanine [21,22]), immune disorders (Felty's syndrome [23], common variable immunodeficiency disorder [24,25]) and myeloproliferative syndromes [26] are associated with NCIPH. The current study suggests that gut disorders are yet another association to be looked for in patients with NCIPH.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatitis with no evidence of viral infection was reported in 43% of patients in two unrelated cohorts (16,17), and raised blood alkaline phosphatase levels were often observed. In most cases, liver biopsy showed mild to moderate periportal lymphocyte infiltration and cholestasis.…”
Section: Cvid and Inflammationmentioning
confidence: 99%